عروض مختصرة - نصر محمد عارف (International Institute of Islamic Thought, 1999)
• Christopher Melchert, The Formation of The Sunni School of Law, 9th-10th Centuries (Leader, Brill, 1997) pp 272. • Richard Yeomams, The story of Islamic Architecture, (London: Garmet Publishing, 1998) pp. 252. • Hasan Kayali, Arabs and Young Truks: Ottomanism, Arabism and Islamism in the Ottoman Empire, 1908-1918 (Berkeley: University of California Press, 1997) pp. 308. • Azmi Ozcan, Pan-Islamism: Indian Muslims, The Ottoman and Britain (1877-1924) (Leiden: Brill, 1997) pp. 237 • - Jakob Skovgaard-Petersn, Defining Islam for the Egyptian State: Muftis and Fatwas of the Dar al-Ifta, Social Economic, and Political Studies of the Middle East and Asia (Leiden: Brill, 1997) pp. 431. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF  في اعلى يمين الصفحة.